2008
DOI: 10.2460/ajvr.69.3.334
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two indirect techniques for local delivery of a high dose of an antimicrobial in the distal portion of forelimbs of horses

Abstract: Both techniques reliably achieved synovial fluid concentrations of amikacin consistent with concentration-dependent killing for bacteria commonly encountered in horses with septic arthritis. Esmarch tourniquets were effective for both delivery techniques in standing horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…concentrations as observed in previous studies [12,19,20]. This variability might in part be explained by the fact that the dose of amikacin was fixed and not corrected for the animal's weight similar to clinical practice and previous studies [21]. Blood contamination of the synovial fluid samples might have affected the measured intrasynovial amikacin concentrations [21].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…concentrations as observed in previous studies [12,19,20]. This variability might in part be explained by the fact that the dose of amikacin was fixed and not corrected for the animal's weight similar to clinical practice and previous studies [21]. Blood contamination of the synovial fluid samples might have affected the measured intrasynovial amikacin concentrations [21].…”
Section: Discussionmentioning
confidence: 87%
“…This variability might in part be explained by the fact that the dose of amikacin was fixed and not corrected for the animal's weight similar to clinical practice and previous studies [21]. Blood contamination of the synovial fluid samples might have affected the measured intrasynovial amikacin concentrations [21]. However, arthrocentesis of the middle carpal joint is regarded as easy [11] and all arthrocenteses were performed by the primary author in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that RLP using the palmar digital (PD) vein delivers therapeutic concentrations of antimicrobial drugs to the distal portion of the limb (Murphey et al, 1999;Rubio-Martinez et al, 2005a;Errico et al, 2008). Multiple treatments using RLP are often needed to resolve persistent infection, and premature termination of RLP is likely to occur because of loss of venous access to the PD vein (Butt et al, 2001;Mattson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%